Risk communication as an operation meant to produce and share audiences - Korbas-Magal, Daniela (MedieKultur: Journal of media and communication research, 2010)
In this article, Luhmann’s system theory is used as a theoretical framework for analysing the way risk communicators view their social functions. Narrated experiences from risk communicators in practice facilitate an understanding of risk communication as both an external irritation to society and part of the mass communication system. They also aid in clarifying how perceptions of audiences are reflected in the risk-communication strategies. The analysis is based on qualitative data collected from in-depth interviews conducted with 22 risk communicators (scientific professionals, spokespeople and journalists) in Israel. Thematic areas reflected in interviewees’ reported strategies embody their perception of audiences. Those themes include: the reduction of complexities; coding and sorting of information; autopoiesis (realisation/non-realisation of the risk); rationality; inherent paradoxes; and schema formation. In sum, the findings suggest that risk communicators play a major role in defining, creating and producing audiences for the mass communication system.